Analysis of healthy life styles and nutritional attitudes of football referees during the pandemic - Karagun, Elif; Selvi, Sabit; Sarper Kahveci, Muge (Progress in Nutrition, 2021)
Study Objectives: This study aims to identify healthy lifestyles and nutritional attitudes of football referees. It intends to analyze these traits based on age, gender, marital status, economic standing, growing plants or keeping a pet at home, having a hobby, doing sports during COVID-19, the term and level of refereeing. Methods: All of the 261 football referees in the province of Kocaeli were attempted to be reached for the study. 202 people from this population volunteered to participate in the study. Since the data were normally distributed, t-test and variance analysis were used. Results: As a result, the healthy lifestyle behaviors scale for the referees doing sports during the COVID-19 pandemic, was found to be statistically significant in the health responsibility, physical activity, psychological development, and interpersonal relationships sub-dimensions and total. Conclusion: As for the females; their scores for the sub-dimensions of attitude towards healthy nutrition, positive nutrition, information on nutrition, emotion for nutrition and malnutrition, and total scores were found to be significantly high. Malnutrition scores were found to be higher for the referees who lived alone compared to those living with their families.